Application of Lean Management in Chinas Manufacturing Industry: A case study on Zhejiang Chenlong Sawing Machine Group. - zheng, wenjie (2006)
This report, which was required by the University of Nottingham Business School as the postgraduate dissertation, is aiming to use a case study on one Chinese manufacturer to reflect how Lean Management is being applied within Chinas manufacturing industry. This objective would be achieved by comparatively analyzing the primary data, which was collected by the interviews and participant observation, as well as the secondary data, which had already been researched by famous scholars. In Chapter 5, the conclusion on the question raised above would be drawn and challenges within Chinas manufacturing industry and further recommendations would also be given.